ERRATUM - Rhona Sharpe (Association for Learning Technology, 2007)
Ellis, R., Goodyear, P., O'Hara, A. & Prosser, M. (2007) The university student experience of face-to-face and online discussions: coherence, reflection and meaning, Alt-J, 15(1), 83–97.